(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2011)
Is to obtain competitive advantage legitimate objective pursued by all organizations to achieve, because they live today in environments of rapid change and dynamic in order to meet the demands of the customer changing as well as intense competition between the organizations, which requires them to get the location of competitive markets in order to do this will remain to do the building and strengthening competitive advantage to be able to achieve, but that this feature is not easy and is not only through the identification and use of a successful strategy for a competitive standard and then manage it successfully. Hence the research problem of determining the sources of differentiation strategy and its impact on the dimensions of competitive advantage compared between the companies maintenance service, which was chosen as a society to conduct the study, namely, (Bladi a company for my car services and machinery Co., Ltd., and Baghdad Car Maintenance Ltd. and Kia Iraqi international Commercial trade agencies). So it grew out of this research to determine the importance of highlighting the actual role of general strategies and specific differentiation strategy to achieve competitive advantage for organizations, as one of the main pillars of the task that must be based upon the national economy, after growing competition in the environment industry due to the entry of goods in foreign markets in recent times, as the way which enhances the prestige of the Organization in the turbulent environment, and meet the challenges to stay away from the traditional method of competition during the break rules, and build sustainable competitive advantage that can not be replicated or reproduced benefits, and this reinforces the importance of research to improve the performance of Iraqi firms. Therefore, the research aims to study the reality of companies maintenance service and diagnosis of their core competencies in building a differentiation strategy that achieve competitive advantage in the industrial sector, the study of the negative aspects avoided by finding appropriate solutions to them. And to identify the ability of Iraqi organizations in achieving competitive advantage over its competitors, by building a sound strategy of differentiation. So you must test the relationship between the moral and strategic differentiation and competitive advantage, so as to enhance understanding of management on this subject. To achieve the objectives of the research, two hypotheses were formulated two main "There is a significant correlation between the dimensions of competitive advantage and differentiation strategy." And "The differentiation strategy a positive influence in the dimensions of competitive advantage." They found a set of conclusions, including: The back of each company in the researched companies were able to gain a competitive edge, but the dimensions are different from the other to varying degrees, allowing them an opportunity to strengthen these dimensions in order to continue and grow. And the emergence of a strong correlation to some extent between the dimensions of competitive advantage and differentiation strategy, where it came from Bladi Company ranked first in terms of interdependence of variables and then Baghdad, a company refers to the coherence variables greatly and effectively. The International Corp. Iraqi trade agencies were the results indicate the existence of linkages acceptable but need to activate, in some dimensions more to make the coherence between the dimensions of competitive advantage and the differentiation strategy more effectively. he most important recommendations is to raise awareness of the importance of Tradition companies pursued a strategy of differentiation through which it can achieve a competitive edge to survive and continue. Finally, must be the philosophy of lowering costs and delivery performance of the all the companies maintenance service and attention to quality through the provision of services beyond customer expectations, and have the company’s ability to change the type of service according to customer needs, and adopt the service companies innovation priority, competitive through its focus on research and development.